2021
DOI: 10.1371/journal.pone.0259165
|View full text |Cite
|
Sign up to set email alerts
|

Targeted proteomics as a tool to detect SARS-CoV-2 proteins in clinical specimens

Abstract: The rapid, sensitive and specific detection of SARS-CoV-2 is critical in responding to the current COVID-19 outbreak. In this proof-of-concept study, we explored the potential of targeted mass spectrometry (MS) based proteomics for the detection of SARS-CoV-2 proteins in both research samples and clinical specimens. First, we assessed the limit of detection for several SARS-CoV-2 proteins by parallel reaction monitoring (PRM) MS in infected Vero E6 cells. For tryptic peptides of Nucleocapsid protein, the limit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
2
25
0
Order By: Relevance
“…Notably, LC-MS/MS proteomics has identified specific proteins and protein-protein interactions linked to mild and severe COVID-19 cases. Upregulation of heparin cofactor II and downregulation of cubilin are associated with COVID-19 severity [9]. Differential regulation of 27 proteins discovered through LC-MS/MS was likewise linked to COVID-19 severity [10].…”
Section: Mass Spectrometry and Proteomicsmentioning
confidence: 96%
“…Notably, LC-MS/MS proteomics has identified specific proteins and protein-protein interactions linked to mild and severe COVID-19 cases. Upregulation of heparin cofactor II and downregulation of cubilin are associated with COVID-19 severity [9]. Differential regulation of 27 proteins discovered through LC-MS/MS was likewise linked to COVID-19 severity [10].…”
Section: Mass Spectrometry and Proteomicsmentioning
confidence: 96%
“…In this context, the results provided by patients’ sputum, complementary to those given by nasopharyngeal and/or throat swabs, allow to better explore the biological factors contributing to COVID-19 severity and to identify potential predictive biomarkers. In a very interesting methodological work, Bezstarosti et al [ 21 ] demonstrated that targeted proteomics has the potential to identify SARS-CoV-2 proteins with sufficient sensitivity for clinical diagnostic labs in which mass spectrometry equipment is available. After assessing, by parallel reaction monitoring (PRM) MS, the limit of detection for several SARS-CoV-2 proteins in infected Vero E6 cells, they estimated that this limit for tryptic peptides of nucleocapsid proteins was in the mid-attomole range.…”
Section: Sputum Proteomics To Investigate Sars-cov2mentioning
confidence: 99%
“…Among these 14 peptides, two peptides of the N protein were selected as attractive candidates [75]. Interestingly, the same target peptides were confirmed by independent groups using the PRM method [107,108]. However, neither approach could overcome the problems of the low detection rate (approximately 20% of the PCR assay) and low throughput analysis (20 min per sample).…”
Section: Application Of Lc-ms/ms For Covid-19 Diagnosismentioning
confidence: 99%